Antidepressant use during pregnancy and gestational diabetes: a systematic review (Research, Society and Development, 2022)
A high number of women are exposed to antidepressants during pregnancy. Considering that an association between exposure to antidepressants and type 2 diabetes was found in the general population and pregnant women are inherently susceptible to insulin resistance, this study aimed to investigate data in the scientific literature on the association between antidepressant use during pregnancy and the risk of developing gestational diabetes mellitus (GDM). This systematic review was conducted according to the PRISMA guidelines. PubMed, Virtual Health Library (VHS), and Web of Science databases were searched to identify observational studies reporting the association between antidepressant use during pregnancy and GDM. Review articles, case reports, case series, clinical trials, and animal studies were excluded. In total, 67 studies were retrieved, of which 3 were included in the systematic review: one case-control and two cohort studies. According to the Newcastle-Ottawa Scale, the three studies were considered high-quality. Through this systematic review, selective serotonin reuptake inhibitors (SSRI) use during pregnancy is not significantly associated with a higher risk of developing GDM. There are still controversies about the association between serotonin and norepinephrine reuptake inhibitors (SNRI) and GDM. The use of tricyclic, tetracyclic, and atypical antidepressants by pregnant women appears to be associated with GDM. Therefore, the available information about the topic is scarce and the condition of further studies is needed.